The Influence Of Religiosity, Technology, Trust, Education, and Income of Gen-Z On Interest in Infaq Using Digital Platforms (QRIS) Using The Probit Method Approach - Arum Teguh Fitriyani; Anton Bawono (CV. Ulil Albab Corp, 2024)
The rapid development of technology has significantly changed the economy, from being conducted directly to now being possible online. One example is the donation payment using QRIS, where transactions can be made simply by scanning a QR code. This study is interesting to investigate because there are relatively few studies related to the interest in donating using digital platforms (QRIS) viewed from the aspects of technological influence, religiosity, income, education, and trust. This research is a quantitative study, using 101 Generation Z samples. The analysis test in this study uses the probit method approach, with the research results showing that religiosity has a significant positive effect on the interest in infaq using QRIS. Technology has a significant negative effect on the interest in infaq using QRIS. Trust has a significant positive effect on the interest in infaq using QRIS. Education has no effect on the interest in donating using QRIS. Income has no effect on the interest in infaq using QRIS.